Cross-Cultural Design. Cultural Differences in Everyday Life 5th International Conference, CCD 2013, Held as Part of HCI International 2013, Las Vegas, NV, USA, July 21-26, 2013, Proceedings, Part II - Rau, P.L.Patrick.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This is the second part of the two-volume set (LNCS 8023-8024) that constitutes the refereed proceedings of the 5th International Conference on Cross-Cultural Design, held as part of the 15th International Conference on Human-Computer Interaction, HCII 2013, held in Las Vegas, USA in July 2013, jointly with 12 other thematically similar conferences. The total of 1666 papers and 303 posters presented at the HCII 2013 conferences was carefully reviewed and selected from 5210 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. This two-volume set contains 113 papers. The papers in this volume focus on the following topics: cultural issues in business and industry; culture, health and quality of life; cross-cultural and intercultural collaboration; culture and the smart city; cultural differences on the Web.
Table of Contents – Part II -- Cultural Issues in Business and Industry -- Research Facing Interface Design of Android System Industrial Control System -- Developing Customer Experience Ecosystem – Driving Business Results by Integrating Multiple Touch Points -- Consumers’ Evaluation and Perception within the Trend of Cultural Creative Design -- Introducing Human Performance Modeling in Digital Nuclear Power Industry -- Exploring Consumers’ Responses to Delayed Introduction of a New Mobile Phone -- The Impact of Workplace Gossip on Organizational Cynicism: Insights from the Employment Relationship Perspective -- A Study of the Effects of Display Atmospherics and Control Mode of 3D Virtual Store on Consumer Behavior in the Elderly -- The Difference of User Perception between Similarity and Dissimilarity Judgments -- Cloud Computing Adoption Journey within Organizations -- Culture, Health and Quality of Life -- Moderating Effect of Culture on IT and Health Standard: A Country-Level Analysis -- Predicting Mental Health Status on Social Media: A Preliminary Study on Microblog -- Designing a Metal Hydride Actuator with Human-Compatible Softness and High Power-to-Weight Ratio for Future Quality-of-Life Technologies -- Design and Assessing the Usability of an Interactive Digital Game in Assisting the Older Adult’s Prescriptive Medication Behavior -- Cultural Diversity - New Challenge to Medical Device Use Safety for International Markets -- Technology-Based Medical Interpretation for Cross-Language Communication: In Person, Telephone, and Videoconference Interpretation and Their Comparative Impact On Limited English Proficiency (LEP) Patient and Doctor -- Toward a Virtual Companion for the Elderly: Exploring the Behaviors that Potentially Achieve Rapport in Human Communication.-Improvement Research of Shoe-Type Measurement Device for a Walking Rehabilitation Support System -- Influence of Organizational Culture and Communication on the Successful Implementation of Information Technology in Hospitals -- The Interaction between Human and the Home Service Robot on a Daily Life Cycle -- Cross-Cultural and Intercultural Collaboration -- Extending Role of “I” Virtually – Identity Performance and Their Influence on Individual Behaviour and Team Performance in Globally Distributed Work Virtual Teams -- Diversity in Unity - How Industry Policy Shaping UI/UX Research -- The Research on Knowledge Diffusion Based on Small World Network -- Implement User-Centered Design in Internationally Distributed Design Teams -- Supporting Globally Distributed Work - Cultural Adaptivity Meets Groupware Tailorability -- Mobile Application Development in FLOSS Platform: A Collaborative Network Approach -- Uncovering the Effects of Cultural Intelligence on Cross-Cultural Virtual Collaboration Processes -- On Relationship between Self-construal and Individual Behavior in Video-Mediated Multicultural Group Decision Making -- Trust and Coordination in Offshore Outsourcing: An Account of Intercultural Collaboration in a Danish and Indian IT Context -- Culture and the Smart City -- The Impact of an Actual Visit and Photograph Watching of an Exhibition on Visitor Viewing Experience -- Designing Urban Experience for Beijing in the Context of Smart City -- A Log Analyzer of Public Transit Guidance Service to Improve a Route Bus Service -- Urban Phenomenology: Incorporating Dynamic Frames of Reference in the Design of Urban OS -- Mixed Factorial Analysis of In-Vehicle Information Systems: Age, Driving Behavior, and Task Performance -- e Innovative PSS Design of Urban Transportation Based on Sharing Style -- Study on Aggressive Driving Activities at Crossroads in Beijing -- Constructing Interaction Scenarios of High-Building Interior in Fire -- SoLoMo User Experience Study Using a Pivoted Parallel Coordinates -- GeoCity Beijing: Platform of Eco-City Information Visualization and Interactive Narrative Structure -- Cultural Differences on the Web -- Comparison of Trust on Group Buying Websites between American and Chinese Young Adults -- How to Make Friends in Social Network Service? A Comparison between Chinese and German -- Smart Mobile Devices in Lifestyles under Transformation: A Comparative Study of Smart Communication among Youth in Hong Kong and Beijing -- Incorporating Culture in Website Design: A Comparison of Taiwanese and Australian Website Characteristics.-Localization of Web Design: An Investigation of Culturally Preferred Web Attributes in Taiwan and the UK.-Communication and Social Network Requirements of Chinese Elderly People for Mobile Services -- Arabic Website Design: User Evaluation from a Cultural Perspective -- Two Sites, Two Voices: Linguistic Differences between Facebook Status Updates and Tweets.-Do We Need a New Internet for Elderly People? A Cross-CulturalInvestigation -- Developing a Contextual Network for Indigenous Communities in Mexico.-A Study of Cross-Culture for a Suitable Information Feeding in Online Social Networks.-A Cross-Cultural Study of User Experience of Video on Demand on Mobile Devices.-A Comparison of Eye Movements When Searching Web Pages between Americans and Koreans.
Keywords: User interfaces (Computer systems).; Computers and civilization; Health informatics; Information storage and retrieval; Application software; Computer science; User Interfaces and Human Computer Interaction; Computers and Society; Health Informatics; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Computer Science, general